PEMANFAATAN MEDIA SOSIAL INSTAGRAM DAN TIKTOK SEBAGAI SARANA PROMOSI SEKOLAH DI ERA DIGITAL STUDI DI MTS YPK CIJULANG - Sahrul Romansah; Andri Dian; Suklani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of digital technology has forced educational institutions to adjust their promotional approaches. Social media platforms such as Instagram and TikTok have emerged as very useful communication tools for reaching a wide audience, especially young people. This study aims to examine the use of Instagram and TikTok as promotional channels at MTs YPK Cijulang, while assessing their influence on the school's reputation and appeal. The method applied is a descriptive qualitative approach, with data collection through direct observation, in-depth interviews, and related documentation. The findings reveal that the use of these two platforms plays an important role in increasing the school's exposure, building a positive image of the institution, and attracting the attention of prospective students and their parents. Content highlighting student activities, academic achievements, and Islamic values proved to be key elements in the success of the school's digital promotion. This study suggests that social media management should be carried out consistently and optimally as a strategic step for school promotion in today's digital age.